Phytomass decomposition of cover crops subjected to mechanical management and soybean yield (Research, Society and Development, 2022)
The research had as objective to evaluate the crops residues decomposition of cover crops mechanically managed and its effect on the soybean yield cultivated in succession. The design used was randomized blocks in a factorial arrangement (5 x 2), subdivided over time, with four replications, consisting of five soil covers (black oats, turnip, turnip + oats, common vetch and fallow) and two forms of species management (knife-roller and shredder). The six collection times (0, 20, 40, 60, 80 and 110 days after management- DAM) were the subplots. The straw decomposition time was evaluated using the litter bags method. At 110 DAM, the covers that showed the greatest decomposition were vetch and fallow (91 and 90%) as well as the shortest half-life-T½ (31 and 33), evidencing their low soil protection. The cover that remained the most was black oats (35%) being a good option to keep the soil covered. In the first 60 DAM, the shredder accelerated the dry matter decomposition by 40% and presented a lower T½ (45). The cover crops cultivation and its management before soybean cultivation did not influence grain yield.